A Simplified Technique for Drainage of Chronic Calcified Pleural Empyema - Rabiou, Sani; Younssa, Hama; Didier, James; Ibrahim, Magagi; Harissou, Adamou; Adakal, Ousseini; Sani, Rachid (The Thoracic and Cardiovascular Surgeon, 2017)
Chronic pleural pocket has well-known diagnosis and treatment principles since first described by Hippocrates 2,400 years ago. However, its treatment remains constant even though its causes, severity during management, and terrain vary considerably. In well-structured health care systems, posttuberculous empyema has become rare; its well-codified medical treatment relies on early diagnosis and adapted antibiotherapy, punctures/drainage, and appropriate intrapleural antifibrinolytics. In developing countries, a poor health organizational system increases the incidence of pleural pocket, which can progress until surgery is indicated. In such a context, the general principles of treatment include pleural decortication along with pulmonary resection. This technique remains difficult, risky, and, sometimes, impossible due to the chronicity of the lesion. In patients debilitated by several months of septic evolution, a simplified thoracostomy technique permits complete resection of the pocket.
Keywords: tuberculosis; thoracic empyema; pyothorax; thoracostomy